Two new species of Pachira (Bombacoideae, Malvaceae) and typification of Pachira patinoi - Vania Nobuko Yoshikawa; William Surprison Alverson; Marília Cristina Duarte (Rodriguésia, 2023)
Abstract We aimed to describe two new species endemic to Brazil - one from sandy habitats in northeastern Brazil (Pachira inaequalivalvis), mainly characterized by fruits with unequal valves, and the other from Amazonian rainforest (P. deflexifolia, having the downward-oriented leaflets) - and provide complete morphological descriptions, illustrations, comments, conservation status, and distribution maps. We also designate a lectotype and an epitype for Pachira patinoi.